KOMUNIKASI PENYULUHAN KURSUS CALON PENGANTIN OLEH BADAN PENASEHATAN PEMBINAAN DAN PELESTARIAN PERKAWINAN (BP4) PEKANBARU - Suprianto "; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Every married couple certainly wants a marriage that is sure to be a sakinah, mawaddah and warahmah. However, there are quite a number of marriages which then end in divorce. One of the efforts made by the government is implementing a bride and groom course program that is run by the Marriage Guidance for the Development and Conservation (BP4). The purpose of this study was to determine the selection of communicators, the messages conveyed, the media used, the objectives, and the effects of communicating information on bride and groom courses by the Agency for Marriage Guidance and Preservation (BP4) Pekanbaru.This study uses a qualitative method, where the selection of informants uses purposive techniques, by interviewing the chairman, administrative staff, and instructors and accidental sampling techniques to interviewing bride and groom course participants. To get the desired data, the researcher made observations first, followed by informant interviews and documentation. Analyzing the data obtained using Huberman and Miles data analysis techniques, the Interactive Data Analysis Model that consists of four stages: data collection, data reduction, data display, conclusion/verification. To achieve the validity of the data, researchers used an extension of participation and triangulation.The results showed that communicators in counseling were people who had broad and certified insights from various circles, including: religious leaders, practitioner academics, health workers, and psychologists. The message conveyed in counseling is informative and persuasive, namely providing material about marriage and inviting participants in the future not to do things that can damage the household and cause divorce. To support counseling to run smoothly, BP4 Pekanbaru uses brochures and the internet to socialize, and other media such as modules, PC, power points, images, infocus, microfon, blackboards in its implementation. Communicating from the counseling of bride and groom courses is the couple who will get married. The effect caused after this counseling is a change or difference in the knowledge and feelings of the bride and groom regarding household life between before and after taking the course. Keywords: Communicating Information,  Bride and Groom Courses, Marriage Guidance and Preservation Agency.